Pengaruh Kualitas Pelayanan, Harga, Lokasi Terhadap Keputusan Pembelian Jasa Kursus Pada Lkp Delta Di Kabupaten Kulon Progo - Mulyono, Agus; Wahyudi, Danang; Nur Rohman, Muhammad Aziz; Sunyoto, Danang (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The target of education is humans, education intends to help students to develop their human potentials. Education is not only found in schools, from birth and in the family it can be called education. The course is an out-of-school education unit consisting of a group of people who provide certain knowledge, skills and attitudes for residents to learn. This study aims to determine the effect of service quality, price, and location on purchasing decisions at LKP Delta in Kulon Progo Regency, Special Region of Yogyakarta. Through purposive sampling method determined the number of samples of 100 respondents. Data collection was carried out by distributing questionnaires to respondents who were participants in the LKP Delta course in 2020. The data analysis method was assisted by the IBM SPSS 22 program to test the relationships between variables. The results of the study stated that service quality and location had a positive effect on purchasing decisions, while prices did not have a positive influence on purchasing decisions.